Prevalence of Gynecological Related Symptoms and Quality of Life in Women Living with HIV/AIDS: a Secondary Analysis from an Online, Cross-Sectional Survey in China - Xie M; Wang A; Lin Z (Dove Medical Press, 2022)
Meilian Xie,1,2 Aiping Wang,1 Zhaoxia Lin3 1Department of Public Service, the First Affiliated Hospital of China Medical University, Shenyang, Liaoning Province, People's Republic of China; 2Department of Nursing, Beijing Ditan Hospital Capital Medical University, Beijing, People's Republic of China; 3Infection Center, Beijing Ditan Hospital Capital Medical University, Beijing, People's Republic of ChinaCorrespondence: Aiping Wang, Department of Public Service, the First affiliated Hospital of China Medical University, Shenyang, People's Republic of China, Email jianghaoran88@hotmail.comObjective: Our study aims to completely understand the experience of gynecological related symptoms (GRS) and the association between GRS and quality of life (QOL) among HIV-infected women in China.Design: A cross-sectional, multicenter survey.Setting: The HIV/AIDS designated medical institutions of seven regions in China.Participants: One hundred and fifty-three women with HIV infection.Primary and Secondary Outcome Measures: Primary outcome measures included the score of GRS and QOL from analysis sample.Results: Among 153 participants, 60.13% were asymptomatic, and 39.87% were symptomatic according to their self-report data. In the symptomatic group, 47.54% reported only one symptom, 18.03% reported 2 symptoms, others reported more than 3 symptoms. The most common symptoms were vaginal discharge (25.49%), followed by irregular period (18.95%), bad cramps (13.07%), vaginal odor (11.11%), and vaginal itching (10.46%). The mean score of QOL was 86.82 ± 15.53. The symptomatic group had higher score than the asymptomatic group on each domain of QOL. GRS were negatively correlated with QOL after adjustment for confounding factors. Correlation matrix of GRS and six domains of QOL demonstrated significant negative correlation with each domain of QOL, especially the most strongly negative correlation with physical function of participants. But the association between GRS and environmental domain was weaker.Conclusion: These findings present the multidimensionality of common gynecologic related symptoms and highlight the clinically meaningful associations between GRS and quality of life among women with HIV infection in China. There is an urgent need to take measures to increase vaginal care and education in advance, delivered by trusted health professionals.Keywords: women living with HIV/AIDS, symptoms, gynecologic related symptoms, quality of life